A Distributed Active Set Method for Model Predictive Control. Issue 3 (2021) - Stomberg, Gösta; Engelmann, Alexander; Faulwasser, Timm
Abstract: This paper presents a novel distributed active set method for model predictive control of linear systems. The method combines a primal active set strategy with a decentralized conjugate gradient method to solve convex quadratic programs. An advantage of the proposed method compared to existing distributed model predictive algorithms is the primal feasibility of the iterates. Numerical results show that the proposed method can compete with the alternating direction method of multipliers in terms of communication requirements for a chain of masses example.